Gonococcal arthritis caused by auxotype P in a man with HIV infection. Issue 2 (April 1990) - Moyle, G; Barton, S E; Midgley, J; Rowe, I F; Keat, A C; Lawrence, A G
Abstract : The development of gonococcal arthritis is reported in a man with HIV infection and CDC Stage IVC2 disease. The diagnosis of disseminated Neisseria gonorrhoeae was facilitated by microbiological examination of a joint aspirate. The auxotype identified by culture was moderately resistant to penicillin, a characteristic which is highly unusual for an organism causing disseminated gonococcal infection. This case serves as an example of the role of HIV infection in the modification of host response to common pathogens and the need for clinicians to modify their management of disseminated gonococcal infection especially in immunosuppressed persons.